Ein neues Buch zu Kaukasisch-Iberien in der Spätantike - Schottky, Martin (Anabasis. Studia Classica et Orientalia, 2020)
The article discusses the content of the book written by Frank Schleicher, titled Iberia Caucasica. Ein Kleinkönigreich im Spannungsfeld großer Imperien (Forum historische Forschung: Antike, Stuttgart: Kohlhammer 2021, 643 pp.). The book consists of eight primarily parts, focused on the Caucasian Iberia, especially from the Hellenistic Period to Late Antiquity. They concern, among other, sources for the region, its geopolitical space, social, political and administrative structures, cultural and religious conditions, and economic aspects as well.